Buildings and Bibles Between Profanization and Sacralization: Semiotic Ambivalence in the Protestant Dutch Bible Belt - Pons-de Wit, Anneke (Material religion, 2019)
Based on an ethnographic case study of three recently erected church buildings in the Dutch Bible Belt, this article demonstrates how orthodox Reformed congregations in the Netherlands define church buildings-especially the auditoria-and bibles as simultaneously profane and mediating the sacred. These at first glance ambivalent discourses are informed by a particular semiotic ideology, which maintains that material spaces and objects like these are sacralized if, and only if, individual believers can meaningfully relate them to their personal spiritual experiences. This ideology makes a primary attitude of profanization of material forms indispensable, because any preexistent sacredness of matter would precisely rule out these personal spiritual experiences.